Restorative Therapies for Erectile Dysfunction: Position Statement From the Sexual Medicine Society of North America (SMSNA). Issue 3 (15th May 2021) - Liu, James L.; Chu, Kevin Y.; Gabrielson, Andrew T.; Wang, Run; Trost, Landon; Broderick, Gregory; Davies, Kelvin; Brock, Gerald; Mulhall, John; Ramasamy, Ranjith; Bivalacqua, Trinity J.
Abstract: Introduction: Current non-invasive treatments for erectile dysfunction (ED) include oral medications, intracavernosal injections, and vacuum-assisted devices. Though these therapies work well for many, a subset of patients have contraindications or are unsatisfied with these options. Restorative therapies for ED are a new frontier of treatments focused on regenerating diseased tissue and providing a potential "cure" for ED. Aim: The aim of this position statement is to examine existing clinical trial data for restorative therapies and identify elements that require further research before widespread adoption. Methods: A literature review was performed to identify all clinical trials performed with regenerative therapy for ED. This includes treatments such as stem cell therapy (SCT), platelet rich plasma (PRP), and restorative related technologies like low-intensity shockwave therapy (LiSWT). Main Outcome Measures: Most clinical trials in restorative therapies were assessed for safety, feasibility, or efficacy. This included recording adverse events, changes in sexual function and erectile function questionnaires, and diagnostics measures. Results: To date there is an absence of robust clinical data supporting the efficacy of restorative therapies regarding ED, though technologies such as LiSWT have established relative safety. Conclusions: Restorative therapies are a promising technology that represents a new frontier of treatment geared towards reversing disease pathology rather than just treating symptoms. However, current published clinical studies are limited. Future work needs to be adequately powered, multi-center, randomized, sham/placebo-controlled trials in well-characterized patient populations to ensure safety and demonstrate efficacy. Until these studies are done, restorative therapies should be reserved for clinical trials and not offered in routine clinical practice.